A demand-oriented approach for integrating earth-to-air heat exchangers into buildings for achieving year-round indoor thermal comfort. (15th February 2019) - Yang, Dong; Wei, Haibin; Shi, Rui; Wang, Jilibo
Highlights: New inverse approach for integrating earth-to-air heat exchangers into buildings described. Engineering parameters inversely calculated for indoor environment year-round thermal comfort. Developed approach avoids overly conservative employment of earth-to-air heat exchangers. Application of earth-to-air heat exchangers is a route to nearly-zero-energy buildings. Abstract: Earth-to-air heat exchanger (EAHE) is a promising energy-efficient technology for indoor thermal environment regulation; however, it should adapt to both building and climatic conditions. This paper proposes a new inverse approach to determine the parameters of EAHE integrating into buildings and to achieve a prescribed indoor thermal comfort objective. First, the criterion for achieving year-round thermally comfortable indoor air temperatures is formulated. According to the objective, the required combined parameters characterizing the dynamic behavior of the earth-to-air heat exchanger outlet-air temperature are inversely calculated. Then, the earth-to-air heat exchanger parameters, such as length, radius, burial depth and flow rate, satisfying the proposed objective are determined. The results demonstrate that decreasing the phase shift of the anticipated indoor air temperature profile helps to reduce the requirements on earth-to-air heat exchanger parameters. A Computational Fluid Dynamics simulation incorporated with real meteorological date is implemented according to the EAHE parameters obtained from the proposed approach. It is demonstrated the proposed inverse approach is effective and the year-round indoor thermal comfort is achievable.